2020
DOI: 10.1073/pnas.2004405117
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic conversion of leaf chloroplasts into carotenoid-rich plastids reveals mechanistic basis of natural chromoplast development

Abstract: Plastids, the defining organelles of plant cells, undergo physiological and morphological changes to fulfill distinct biological functions. In particular, the differentiation of chloroplasts into chromoplasts results in an enhanced storage capacity for carotenoids with industrial and nutritional value such as beta-carotene (provitamin A). Here, we show that synthetically inducing a burst in the production of phytoene, the first committed intermediate of the carotenoid pathway, elicits an artificial chloroplast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 47 publications
2
127
0
Order By: Relevance
“…In this way, any changes in carotenoid composition always lead to abnormal plastid development (Park et al, 2002;Welsch et al, 2000). Recently, the expression of a bacteria CrtB (PSY) gene (in Arabidopsis, lettuce, tobacco, and zucchini), and as a consequence of that, a burst in phytoene accumulation, was shown to stimulate differentiation of chloroplast into chromoplast suggesting that indeed carotenoid content influences chloroplast development (Llorente et al, 2020). Interestingly, we observed increased chloroplast number in our transplastomic tobacco lines (Table S4), which is in line with the increased chromoplast number observed in tomato fruits expressing the citrus LCYB gene (Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, any changes in carotenoid composition always lead to abnormal plastid development (Park et al, 2002;Welsch et al, 2000). Recently, the expression of a bacteria CrtB (PSY) gene (in Arabidopsis, lettuce, tobacco, and zucchini), and as a consequence of that, a burst in phytoene accumulation, was shown to stimulate differentiation of chloroplast into chromoplast suggesting that indeed carotenoid content influences chloroplast development (Llorente et al, 2020). Interestingly, we observed increased chloroplast number in our transplastomic tobacco lines (Table S4), which is in line with the increased chromoplast number observed in tomato fruits expressing the citrus LCYB gene (Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplasts are key organelles of plants. In addition to their well-known function in photosynthesis, chloroplasts are also involved in important biological processes such as plant immunity and crop quality [ 9 , 10 ]. The genetic transformation of chloroplasts has become a hotspot in genetic engineering [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously observed that inoculation of zucchini plants with a ZYMV-based vector that expressed P. ananatis crtB (ZYMV-crtB) caused infected leaves to turn bright yellow 5 . We have, more recently, understood that this phenotype is a consequence of the heterologous crtB enzyme inducing phytoene accumulation beyond a threshold that triggers transformation of leaf chloroplasts into chromoplasts, which is accompanied by the accumulation of high levels of downstream carotenoids 6 . To test whether we could trigger the chloroplast-to-chromoplast transformation in fruits, with concomitant carotenoid overaccumulation, we grew seedlings of a zucchini cultivar (MU-CU-16) 13,14 , which produces marketable dark green uniformly cylindrical fruits, and mechanically inoculated the plants (n=3) with ZYMV-crtB at one-week intervals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Virus-based expression of transcription factors Delila and, particularly, Rosea1 from Antirrhinum majus has been shown to lead to massive accumulation of anthocyanins in plant tissues 3,4 . Similarly, virus-based expression of Pantoea ananatis phytoene synthase (crtB), the enzyme catalyzing the first step of carotenoid biosynthesis in this soil bacterium, has been demonstrated to lead to a substantial accumulation of phytoene and other carotenoids in plant tissues 5,6 . Virus-based co-expression of crtB and a Crocus sativus carotenoid cleavage dioxygenase (CCD2L) induced large accumulation in N. benthamiana leaves of the apocarotenoid crocins and picrocrocin, which naturally accumulate in saffron stigma and are main constituents of the valued spice 7 .…”
Section: Introductionmentioning
confidence: 99%